The Evolution of Fraud Detection: A Comprehensive Analysis of AI-Powered Solutions in Financial Security - Sandeep Jarugula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of artificial intelligence on fraud detection and risk mitigation strategies across various industries. Examining the integration of predictive analytics and behavior-based detection systems demonstrates how machine learning algorithms enhance the accuracy and efficiency of fraud prevention. This article delves into the architectural components of AI-driven systems, implementation methodologies, and real-world applications in the banking, insurance, and retail sectors. An article on pattern recognition, user behavior monitoring, and anomaly detection mechanisms, illustrates how these advanced systems adapt to emerging fraud tactics while minimizing false positives. It highlights the significance of continuous learning models and their role in creating robust security frameworks for financial institutions and businesses.